2016
DOI: 10.1007/s00208-016-1375-4
|View full text |Cite
|
Sign up to set email alerts
|

Stability conditions on $$\text {CY}_N$$ CY N categories associated to $$A_n$$ A n -quivers and period maps

Abstract: In this paper, we study the space of stability conditions on a certain N -Calabi-Yau (CY N ) category associated to an An-quiver. Recently, Bridgeland and Smith constructed stability conditions on some CY 3 categories from meromorphic quadratic differentials with simple zeros. Generalizing their results to higher dimensional Calabi-Yau categories, we describe the space of stability conditions as the universal cover of the space of polynomials of degree n+1 with simple zeros. In particular, central charges of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 22 publications
1
22
0
Order By: Relevance
“…Remark Corollary affirms [, Conjecture 1.3] and the second part of [, Conjecture 5.8] (see also [, Corollary 1.2; , Corollary 5.1]).…”
Section: Contractible Stability Spacessupporting
confidence: 72%
“…Remark Corollary affirms [, Conjecture 1.3] and the second part of [, Conjecture 5.8] (see also [, Corollary 1.2; , Corollary 5.1]).…”
Section: Contractible Stability Spacessupporting
confidence: 72%
“…More recently, an extension of the results of Bridgeland-Smith to certain polynomial quadratic differentials on C was carried out in [22,12]. There, CYn categories appear for n ≥ 2.…”
Section: Comparison With the Work Of Bridgeland-smithmentioning
confidence: 99%
“…Later [11], see also [43], showed that it was the universal cover in all these cases. When the underlying Dynkin diagram of Q is A n , [26] shows that Stab(Γ N Q) is the universal cover of the space of degree n+1 polynomials p n (z) with simple zeros. The central charges are constructed as periods of the quadratic differential p n (z) N −2 dz ⊗2 on P 1 , using the technique of [16].…”
Section: Introductionmentioning
confidence: 99%